Microbiome metabolomics reveals new drivers of human liver steatosis. (July 2018) - Delzenne, Nathalie; Bindels, Laure
An integrative multiomics approach in nondiabetic obese women identifies phenylacetate as a microbial metabolite contributing to the accumulation of lipids in the liver and hence to nonalcoholic steatohepatitis.